MODEL ASESMEN PORTOFOLIO, KREATIVITAS, DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - SUKMAWATI SUKMAWATI (Jurnal Evaluasi Pendidikan, 2013)
This research aimed to study the effects of application of the portfolio assessment model and creativity toward the ability of solving mathematics problem (ASMP). This research used Group Within Treatment (GWT) design within experimental method and applied three kinds of treatment, namely: show case portfolios, document portfolios, and working portfolios. Each treatment involved three groups of student from SMAN 1, SMAN 5, and SMAN 14 Makassar. The data analysis used in this research was two-way analysis of variance with GWT. The findings acquired were the difference between the ability of mathematics problem solving of the students who were assessed through showcase portfolios, document portfolios, and working portfolios. For the group of students with high creativity, the ability of mathematics problem solving of those who were assessed with showcase portfolios and document portfolios was higher than those who were assessed with working portfolios. For the group of students with low creativity, the ability of mathematics problem solving of those who were assessed with working portfolios was higher than those who assessed with document portfolios, and showcase portfolioswas higher than showcase portfoliodocument portfolios. The results of this research showed that showcase portfolio assessment can be used as an alternative assessment for problem solving learning.